UTILIZATION OF PLANTAIN WASTE FOR THE PRODUCTION OF SECONDARY METABOLITES BY SOLID SUBSTRATE FERMENTATION USING THE FUNGI Lentinus crinitus - GRANDA R., Diana M.; MEJÍA G., Amanda I.; MEJÍA G., Amanda I.; JIMÉNEZ T., Gloria A.; JIMÉNEZ T., Gloria A. (Vitae, 2009)
<!--[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0;} @font-face {font-family:Calibri; panose-1:2 15 5 2 2 2 4 3 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-1610611985 1073750139 0 0 159 0;} @font-face {font-family:Aldine401BT-RomanA; panose-1:0 0 0 0 0 0 0 0 0 0; mso-font-alt:"MS Mincho"; mso-font-charset:128; mso-generic-font-family:auto; mso-font-format:other; mso-font-pitch:auto; mso-font-signature:3 134676480 16 0 131073 0;} @font-face {font-family:Aldine401BT-ItalicA; panose-1:0 0 0 0 0 0 0 0 0 0; mso-font-charset:0; mso-generic-font-family:auto; mso-font-format:other; mso-font-pitch:auto; mso-font-signature:3 0 0 0 1 0;} @font-face {font-family:Verdana; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:536871559 0 0 0 415 0;} @font-face {font-family:"\@Aldine401BT-RomanA"; panose-1:0 0 0 0 0 0 0 0 0 0; mso-font-charset:128; mso-generic-font-family:auto; mso-font-format:other; mso-font-pitch:auto; mso-font-signature:0 134676480 16 0 131072 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:Calibri; mso-fareast-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; mso-fareast-language:EN-US;} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:Calibri; mso-fareast-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; mso-fareast-language:EN-US;} @page Section1 {size:595.3pt 841.9pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:35.4pt; mso-footer-margin:35.4pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> This paper presents the production of secondary metabolites with pharmaceutical and alimentary interest from plantain waste used as substrate in a solid state fermentation process with the white root fungi Lentinus crinitus. The production of metabolites is studied during the growth of the microorganism for a period of 21 days, in a system conformed by 7 substrate combinations: stem-fruit, leaves -fruit, leaves -stem, leaves, stem, fruit and leaves-stem-fruit. The best combination for the production of enzymes -lignin peroxidase (LiP) and -manganese peroxidase (MnP) is conformed by leaves-stem of plantain Musa paradisiaca. It is then important to take advantage of the huge potential that these residues have for the production of peroxidase enzymes, which have many applications. On the other hand, the use for the first time of the fungi Lentinus crinitus in such production constitutes a novel biotechnological approach. In the systems where there is enzymatic activity (stem-fruit, leaves-fruit, leaves-stem and leaves-stem-fruit) the aromatic compounds: ferulic acid, vanilla, vanillin acid and eugenol are determined at 11, 16 and 21 days by high performance liquid chromatographic (HPLC). For the systems with the best enzymatic activity (leaves-steam), the concentration of aromatic products is low. In the system conformed by leaves-fruit, where only the production of the LiP enzyme is important, significant concentrations of ferulic acid, vanilla, vanillin acid and eugenol are found during the sixteenth day.